Ultrasonographic anatomy of the atlanto‐occipital region and ultrasound‐guided cerebrospinal fluid collection in rabbits (Oryctolagus cuniculus). Issue 2 (20th November 2017) - Anselmi, Carlo; Dias, Sara; Martorell, Jaume; Navarro, Marc; Espada, Yvonne; Novellas, Rosa
Abstract: Cerebrospinal fluid analyses are important for diagnosis of neurologic problems in rabbits and for translational research projects using rabbits as models. Blind puncture of the cisterna magna is the current standard technique for sampling cerebrospinal fluid in this species. However, the complexity and small size of the cisterna magna and surrounding structures are limitations of this technique. Aims of this prospective, anatomic, pilot study were to (1) describe the normal anatomy of the atlanto‐occipital region, (2) describe ultrasonographic anatomic landmarks, and (3) develop and evaluate a technique for ultrasound‐guided puncture of the cisterna magna for cerebrospinal fluid sampling in rabbits. Thirty healthy rabbits were included and the study was conducted in three stages. Three rabbit cadavers were used for the first stage of the study. Then, the second stage was completed using 13 rabbit cadavers. Finally, the third stage was completed in 14 live rabbits. The ultrasound‐guided puncture performed in 13 cadavers was successful at the first attempt in 10 cases, and at the second attempt in the remaining three cases. In the in vivo study, the ultrasound‐guided puncture was successful in all 14 cases, without signs of complications. Findings supported the use of ultrasound‐guided puncture of the cisterna magna as a safe technique that may be used routinely or when the sample of cerebrospinal fluid cannot be obtained with the blind technique in rabbits.